Gustavo Ariel SCHWARTZ - Víctor BERMÚDEZ, eds. "#Nodes. Entangling Sciences and Humanities". Bristol, Intellect Books, 2019, 540 pp. - Foedtke, Friederike (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This review is about the book #Nodes. Entangling Sciences and Humanities, edited by Gustavo Ariel Schwartz and Víctor Bermúdez. #Nodes is a book which aims to bridge the gap between the sciences, humanities, arts, and literature. It brings together a variety of interdisciplinary perspectives on ten issues which have been occupying researchers from all of these fields for a long time: complex networks, metaphor, the cosmos, chaos and complexity, emergence, perception, memory, emotion, consciousness, and big data. Literature plays a key role in this book, not only because it constitutes part of the book, but also because its relations to different scientific fields are highlighted in numerous of the short articles of #Nodes.
Keywords: sciences; humanities; interdisciplinary research; cognitive literary studies; science and literature